Mutation of Gemin5 Causes Defective Hematopoietic Stem/Progenitor Cells Proliferation in Zebrafish Embryonic Hematopoiesis - Liu, Xiaofen; Zhang, Wenjuan; Jing, Changbin; Gao, Lei; Fu, Cong; Ren, Chunguang; Hao, Yimei; Cao, Mengye; Ma, Ke; Pan, Weijun; Li, Dantong (Frontiers in Cell and Developmental Biology, 2021)
Fate determination and expansion of Hematopoietic Stem and Progenitor Cells (HSPCs) is tightly regulated on both transcriptional and post-transcriptional level. Although transcriptional regulation of HSPCs have achieved a lot of advance, its post-transcriptional regulation remains largely underexplored. The small size and high fecundity of zebrafish makes it extraordinarily suitable to explore novel genes playing key roles in definitive hematopoiesis by large-scale forward genetics screening. Here, we reported a novel zebrafish mutant line gemin5cas008 with a point mutation in gemin5 gene obtained by ENU mutagenesis and genetic screening, causing an earlier stop codon next to the fifth WD repeat. Gemin5 is an RNA-binding protein (RBP) with multifunction in post-transcriptional regulation, such as regulate the biogenesis of snRNPs, alternative splicing, stress response and translation control. The mutants displayed specific deficiency in definitive hematopoiesis without obvious defects during primitive hematopoiesis. Further analysis showed impaired definitive hematopoiesis was due to defective proliferation of HSPCs. Overall, our results indicate that Gemin5 performs an essential role in regulating HSPCs proliferation.